Droplet-jet mode near-field electrospinning for controlled helix patterns with sub-10 mu m coiling diameter - Shin, Dongwoon; Kim, Jonghyun; Choi, Sun; Lee, Yong-bok; Chang, Jiyoung (IOP PUBLISHING LTD, 2019)
This study presents a novel droplet-jet mode of near-field electrospinning which allows microscale control of helix patterns using nanofiber. While the cone jet mode has been used to generate a printable nanofiber to date, the cone jet mode requires a high applied voltage with a long jet travel distance to obtain the nanofiber, resulting in a large coiling diameter. In order to integrate the near-field electrospinning into microscale devices, it is important to achieve a comparable nanofiber pattern resolution. Herein, we have demonstrated printing of nanofibers with a coiling diameter of sub-10 mu m, which is produced by the droplet-jet mode of near-field electrospinning. Also, it is found that the coiling diameter, wavelength, and frequency can be controlled by the droplet size as one of the process parameters in the droplet-jet mode. The droplet-jet mode will be a promising near-field electrospinning technique to apply direct-written nanofibers to various micro-scale applications.
Keywords: ELECTROHYDRODYNAMIC JET; NANOFIBER; OPTIMIZATION; DESIGN